Case report on Cabezas syndrome-where hypogonadism and obesity meet intellectual disability - Salodkar, Manan A.; Meshram, Priyanka M.; Azad, Asma K.; Ambatkar, Kanchan K. (International Journal of Research in Medical Sciences, 2024)
The symptom complex of obesity, hypogonadism and developmental delay are common to multiple syndromes. One such rare syndrome is the Cabezas syndrome caused by a wide spectrum of hemizygous variants in CUL4B gene, clinically characterized by myriad findings which include developmental delay/intellectual disability (ID), obesity, hypogonadism, typical and well recognizable somatic dysmorphisms, behavioural disturbances, ataxia and intention tremor. Worldwide, only a handful of cases of this syndrome have been reported in the last twenty-four years and our case is possibly the first reported case of Cabezas syndrome in India.